Pulmonary and urinary clearance of atrial natriuretic factor in acute congestive heart failure in dogs. - Perrella, M A (1991)
Atrial natriuretic factor (ANF) is a peptide hormone of cardiac origin elevated in acute congestive heart failure (CHF), which is degraded by the enzyme neutral endopeptidase 24.11 (NEP). This study was designed to investigate the pulmonary and urinary clearance of ANF before and after the initiation of acute experimental CHF in dogs, and to assess the contribution of enzymatic degradation to these clearances in CHF. This study demonstrated a significant clearance of plasma ANF across the pulmonary circulation at baseline, and a tendency for pulmonary clearance to decrease in CHF (1115 +/- 268 to 498 +/- 173 ml/min, NS). The pulmonary extraction of ANF present at baseline was not altered with acute CHF (36.0 +/- 7.8 to 34.9 +/- 12.1%, NS). NEP inhibition (NEPI) abolished both the clearance and extraction of plasma ANF across the lung in CHF. Similarly, significant urinary clearance of ANF was present at baseline, and in acute CHF the urinary clearance of ANF decreased (0.14 +/- 0.02 to 0.02 +/- 0.01 ml/min, P less than 0.05). NEPI prevented the decrease in the urinary clearance of ANF, and enhanced the renal response to endogenous ANF, independent of further increases in plasma ANF during CHF. This study supports an important role for NEP in the pulmonary and urinary metabolism of endogenous ANF during acute CHF.